2002
DOI: 10.1029/2002gl015304
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of acoustically enhanced solute transport in porous media

Abstract: [1] The effect of acoustic waves on the transport of a conservative tracer in a water saturated column packed with glass beads was investigated. It was observed from the experimental data that the addition of acoustic waves, in the frequency range between 60 to 245 Hz, to a steady background pressure gradient, enhances solute transport compared to the base case consisting of only a background pressure gradient. Furthermore, it was found that the effective velocity of the solute is approximately inversely propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…Experimental studies have shown that acoustic waves enhance dissolved mass transport in saturated porous media (Vogler and Chrysikopoulos, 2002), and also increase dissolution/mass-transfer from single and multicomponent DNAPL ganglia in saturated porous media Vogler and Chrysikopoulos, 2004). Furthermore, several other investigations indicated that vibration of porous media can mobilize DNAPL ganglia (Reddi and Challa, 1994;Reddi and Wu, 1996;Reddi et al, 1998;Roberts et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Experimental studies have shown that acoustic waves enhance dissolved mass transport in saturated porous media (Vogler and Chrysikopoulos, 2002), and also increase dissolution/mass-transfer from single and multicomponent DNAPL ganglia in saturated porous media Vogler and Chrysikopoulos, 2004). Furthermore, several other investigations indicated that vibration of porous media can mobilize DNAPL ganglia (Reddi and Challa, 1994;Reddi and Wu, 1996;Reddi et al, 1998;Roberts et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Resonant behavior of saturated porous media, neglecting motion of porous media parallel to the flow of the interstitial fluid, has been determined to be a function of porosity (Pan and Horne, 2000). A recent experimental study has also shown that acoustic waves enhance solute transport in saturated porous media due to the addition of an oscillatory interstitial water velocity to the background flow field (Vogler and Chrysikopoulos, 2002). The additional oscillatory interstitial flow velocity is caused in part by an out of phase pressure wave (slow wave) compared to the motion of the solid matrix (Biot, 1956a,b).…”
Section: Introductionmentioning
confidence: 98%
“…One of the persistent themes throughout the study is the need to model and predict accurately the coupled solid-fluid and fluid-fluid interactions in porous medium fluid flow related to elastic wave motions, which has practical importance in a wide variety of engineering applications, such as acoustic wave stimulation to enhance hydrocarbon recovery from subsurface environments [3,32] and seismic wave tomography to image oil-bearing formations and NAPL (nonaqueous phase liquid)-contaminated sites [35].…”
Section: Introductionmentioning
confidence: 99%